A prospective randomised multicentre study comparing continuous and intermittent treatment with celecoxib in patients with osteoarthritis of the knee or hip. Issue 1 (30th June 2006) - Luyten, F P; Geusens, P; Malaise, M; De Clerck, L; Westhovens, R; Raeman, F; Vander Mijnsbrugge, D; Mathy, L; Hauzeur, J P; De Keyser, F; Van den Bosch, F
Abstract : Objective: To compare the effects of continuous and intermittent celecoxib treatment in patients with knee or hip osteoarthritis in flare. Methods: In this 24-week, prospective, randomised, double-blind, placebo-controlled study, patients were randomly assigned to receive continuous (n = 62) or intermittent (n = 61) treatment with celecoxib 200 mg once daily. The primary efficacy end point was the area under the curve (AUC) of the change in the Western Ontario and McMaster Universities Osteoarthritis Index (WOMAC) total scores between baseline and week 24 divided by the time interval. Secondary end points included the percentage of days with intake of the flare drug, the AUC of the change in the WOMAC total scores, the mean change from baseline in the WOMAC scores, and the patient's and physician's global assessment of osteoarthritis. Results: There were no significant differences between patients randomised to continuous or intermittent treatment in the primary end point or most of the secondary end points, although a consistent trend supporting continuous treatment was observed. The percentage of days with intake of the flare drug was significantly lower (p = 0.031) in the group receiving continuous versus intermittent celecoxib. Both treatment regimens were well tolerated. Conclusion: The results of this pilot study indicate a potential clinical difference between continuous and intermittent treatment with celecoxib, and may be useful in designing future trials. A larger trial on both efficacy and safety outcomes is required for conclusive evidence in favour of either continuous or intermittent treatment.